Preparation process of titanium carbide
By controlling the pore size and specific gravity of titanium dioxide, and using atomization and drying, preheating and gradient heating processes, the problems of poor mixing uniformity of carbon black and insufficient yield of titanium carbide in the existing titanium carbide preparation process are solved, and high-quality and high-yield preparation of titanium carbide is achieved.
Patent Information
- Application Number
- CN202510571114.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-06
- Publication Date
- 2025-06-03
- Estimated Expiration
- 2045-05-06
AI Technical Summary
In the existing titanium carbide preparation process, the average pore size of titanium dioxide is large and the specific gravity of the stack is low, resulting in poor mixing uniformity of carbon black and insufficient yield of titanium carbide, affecting the quality of the finished product.
By controlling the pore size of titanium dioxide at 1-5nm and the specific gravity of the stack is above 0.8g/cm³, combined with atomization and drying, preheating and gradient heating processes, the carbon black mixing uniformity ≥95% and the titanium carbide yield is increased to above 99.5%.
The quality and yield of finished titanium carbide has been significantly improved, and the uniformity of carbon black mixing and titanium carbide yield have been improved.
Smart Images

Figure CN120081377A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbide preparation, and particularly to a preparation process of titanium carbide. Background Art
[0002] Titanium carbide is an important ceramic material with high hardness, high melting point, excellent wear resistance and electrical conductivity, and is widely used in fields such as cutting tools, wear-resistant coatings and electronic devices.
[0003] As a precursor material of titanium carbide, the purity, particle size and dispersibility of nano-titanium dioxide directly affect the performance of titanium carbide. In the existing titanium dioxide preparation process, the average pore diameter of its product is 18 - 22 nm, the bulk density is only 0.55 g / cm³, and the carbon black mixing index is less than 80%.
[0004] In the titanium dioxide obtained by the spray drying process reported currently, the sulfur content > 0.3%, resulting in a titanium carbide yield of less than 70%; a kind of titanium carbide ceramic microsphere and its high-temperature self-propagating preparation disclosed in Patent Publication No.: CN116654936 A, in which the slurry suspension is sent into a spray dryer, and after high-speed centrifugal atomization, collection and sieving, Ti - C agglomerated powder with a particle size of 35 - 74 μm is obtained, and a titanium carbide ceramic composite powder with a wide particle size range (1 - 50 μm), high product purity and sphericity is prepared.
[0005] However, in actual large-scale industrial production, there will still be problems such as an average pore diameter > 15 nm, a bulk specific gravity < 0.6 g / cm³, resulting in poor carbon black mixing uniformity (mixing index < 85%), a titanium carbide yield < 75%, uneven mixing of carbon black and titanium dioxide in the early stage, and a low titanium carbide yield. Summary of the Invention
[0006] In view of the above problems, the present invention provides a preparation process of titanium carbide, which realizes a carbon black mixing uniformity ≥ 95% and a titanium carbide yield increased to more than 99.5%, greatly improving the quality and yield of the finished titanium carbide.
[0007] To solve the above problems, the technical solution adopted by the present invention is: A titanium carbide preparation process includes the following steps: S1. Select ilmenite with a phosphorus content < 100 ppm, and after crushing, reduction, concentration, hydrolysis, washing, and filtration, generate a titanium dioxide filter cake; control the pore size of titanium dioxide to be 1 - 5 nm, the phosphorus content to be less than 50 ppm, and the sulfur content to be less than 0.1%; S2. Pulp the titanium dioxide filter cake obtained in step S1 to form a primary slurry, add carbon black according to the content of titanium dioxide, and stir evenly to form a secondary slurry; S3. Continuously stir the secondary slurry, and pump the secondary slurry into a spray dryer for atomization drying to generate titanium dioxide - carbon black particles; S4. The titanium dioxide - carbon black particles pass through a high - temperature roasting zone under the action of air flow and gravity to generate titanium carbide powder; wherein, the secondary slurry is pre - heated in a pipeline before spraying, and after spraying, it undergoes two - stage gradient heating to generate titanium dioxide - carbon black particles.
[0008] Preferably, the secondary slurry is pre - heated in a pipeline before spraying to a temperature of 50 - 60 °C, after spraying, it is first heated to 130 - 150 °C, and finally heated to 250 - 280 °C to generate titanium dioxide - carbon black particles. After drying, the moisture content of the titanium dioxide - carbon black particles is < 2%.
[0009] Preferably, a preparation furnace is used. The preparation furnace includes a drying zone at the top and a roasting zone at the bottom. An atomization drying ring is arranged in the drying zone. An annular atomization drying channel is formed inside the atomization drying ring. An atomization spray gun is arranged in the atomization drying channel. While the atomization spray gun atomizes and sprays the secondary slurry, a spiral drying air flow is controlled to be formed in the atomization drying channel to achieve two - stage gradient heating of the titanium dioxide - carbon black particles.
[0010] Preferably, the atomization spray gun includes a nozzle, a spray gun end, and a spray gun base. The nozzle is fixedly connected to the spray gun end, and the spray gun end is rotatably connected to the spray gun base.
[0011] Preferably, the spray gun end includes a pump air channel and a slurry channel. The slurry channel is annular and sleeved outside the pump air channel. The nozzle includes a jet channel communicating with the pump air channel and a liquid spray channel communicating with the slurry channel. The liquid spray channel communicates with the jet channel and is in a cross - state.
[0012] Preferably, the nozzle further includes a spray sleeve communicating with the jet channel. The spray sleeve is eccentrically arranged outside the rotation axis of the spray gun end.
[0013] Preferably, after the ilmenite in step S1 is crushed by ball milling, it is mixed with 98% acid, initiated with distilled water, and reacts to generate a mixture of titanyl sulfate, ferric sulfate, and ferrous sulfate. Then, it is leached with water to dissolve the soluble salts. After leaching, the slurry is reduced with iron powder; after reduction, the slurry is separated by sedimentation, primary filtration, and secondary filtration, and the ferrous sulfide is separated by a freeze - crystallization process.
[0014] Preferably, after the titanium solution separated from iron sulfide is finely filtered, a vacuum concentration process is adopted to control the specific gravity of the titanium solution at 1.575 - 1.585. The specific gravity of the titanium solution is controlled by the total titanium concentration, and the total titanium concentration is 300 - 320 g / L. A pressure hydrolysis process is adopted, and steam is slowly introduced to control the hydrolysis temperature rising rate not exceeding 0.5 °C / min. The metatitanic acid after hydrolysis is subjected to first washing, bleaching, and second washing to control Fe < 30 ppm.
[0015] Preferably, the metatitanic acid after the second washing is pumped into a plate and frame filter press and washed with 3 - 5% ammonia water for 50 - 60 minutes. The content of SO 3 in the plate and frame titanium dioxide is detected, and SO 3 in the plate and frame titanium dioxide is controlled to be < 0.1%. The pore diameter of the titanium dioxide is detected, the pore diameter of the titanium dioxide filter cake is 10 - 12 nm, and the pore diameter of the finished titanium dioxide product is 1 - 5 nm. The washed titanium dioxide filter cake is slurried into a titanium dioxide slurry, and the solid content of the titanium dioxide slurry is controlled at 20 - 25%. The calculated carbon black is added and stirred evenly, and the particle size of the carbon black is 400 - 600 mesh.
[0016] Preferably, the feeding rate of the secondary slurry for atomization drying is 5 - 10 L / min, and the atomization pressure is 0.2 - 0.4 MPa.
[0017] The beneficial effects of the present invention are as follows: Compared with the prior art, by controlling the pore diameter of titanium dioxide (1 - 5 nm) and the bulk specific gravity (> 0.8 g / cm³), and cooperating with processes such as atomization drying, preheating, and gradient heating, the mixing uniformity of carbon black is achieved to be ≥ 95%, and the yield of titanium carbide is increased to more than 99.5%, greatly improving the quality and yield of the finished titanium carbide. Description of the Drawings
[0018] Figure 1 It is a schematic diagram of the internal structure of the silicon carbide preparation furnace of the present invention (the dotted line is the schematic line of the spiral upward movement of the atomized secondary slurry; the solid line is the schematic line of the titanium dioxide - carbon black particles passing through the high - temperature roasting area under the action of air flow and gravity).
[0019] Figure 2 For the present invention Figure 1 The enlarged structural schematic diagram of part A.
[0020] Figure 3 It is a three - dimensional structural schematic diagram of the atomizing spray gun of the present invention.
[0021] Figure 4 It is a schematic diagram of the internal structure of the atomizing spray gun of the present invention.
[0022] Figure 5 For the present invention Figure 4Schematic diagram of the enlarged structure at position B.
[0023] Figure 6 This is the process flow chart of the present invention.
[0024] Figure 7 This is the comparison table of the examples and the comparative examples.
[0025] In the figure: 100, preparation furnace; 200, atomization drying ring; 210, first side plate; 220, second side plate; 230, atomization drying channel; 300, atomization spray gun; 310, spray gun base; 311, first conveying channel; 312, second conveying channel; 320, spray gun end; 321, slurry channel; 322, pump air channel; 330, nozzle; 331, jet channel; 332, liquid spraying channel; 333, spray sleeve. Detailed implementation manners
[0026] The present invention will be further described below in conjunction with the drawings and examples.
[0027] Referring to the attached Figure 6 , a titanium carbide preparation process includes the following steps: Step 1: Select ilmenite with a phosphorus content < 100 ppm. After ball milling and pulverizing, it is mixed with 98% acid, initiated with distilled water, and reacts to form a mixture of titanyl sulfate, ferric sulfate, ferrous sulfate, etc. Then, it is leached with water to dissolve the soluble salts, and the slurry after leaching is reduced with iron powder.
[0028] Step 2: After the reduced slurry undergoes sedimentation, primary filtration, and secondary filtration, the freeze crystallization process (separating ferrous sulfate by low-temperature crystallization to avoid interference of iron impurities in subsequent hydrolysis reactions) is adopted to separate ferrous sulfide.
[0029] Step 3: After the titanium liquid after ferrous separation is finely filtered, the vacuum concentration process is adopted to increase the concentration of the titanium liquid to 300 - 320 g / L (total titanium) to provide a highly active reaction system for subsequent hydrolysis, and the specific gravity of the titanium liquid is controlled at 1.575 - 1.585.
[0030] Step 4: Adopt the pressurized hydrolysis process to hydrolyze titanyl sulfate at high temperature and high pressure to form metatitanic acid: TiOSO 4 + 2H 2 O → H 2 TiO 3 ↓ + H 2 SO 4 , slowly introduce steam, and control the hydrolysis heating rate not to exceed 0.5 °C / min.
[0031] Step 5: The metatitanic acid after hydrolysis is subjected to first washing, bleaching, and second washing to control Fe < 30 ppm.
[0032] Step 6: The washed metatitanic acid after secondary washing is fed into a plate and frame filter press and washed with 3 - 5% ammonia water (which can be replaced by ammonium carbonate or organic amine) for 50 - 60 minutes. Detect the sulfur content of titanium dioxide in the plate and frame, and control the SO 3 <0.1% in the titanium dioxide of the plate and frame, and detect the pore size of titanium dioxide.
[0033] Step 7: The washed titanium dioxide filter cake is slurried into a titanium dioxide slurry, control the solid content of the titanium dioxide slurry at 20 - 25%, add the calculated carbon black, and stir evenly.
[0034] Step 8: The material is dried through a spray dryer, control the final spray drying temperature at 250 - 280 °C, and the moisture content of the dried material is less than 2%.
[0035] Step 9: The titanium dioxide - carbon black particles pass through a high - temperature roasting zone under the action of air flow and gravity to generate titanium carbide powder.
[0036] The titanium dioxide slurry is dried through a spray dryer, control: feed rate 5 - 10 L / min; atomization pressure 0.2 - 0.4 MPa; inlet temperature 250 - 280 °C; outlet temperature 100 - 120 °C; moisture content of the dried material < 2%, and detect the pore size (1 - 5 nm), phosphorus content (< 50 ppm), and sulfur content (< 0.1%) of the finished titanium dioxide.
[0037] When the atomization pressure of the secondary slurry is 0.4 MPa, match the feed rate of 5 - 6 L / min; when the atomization pressure is 0.2 MPa, match the feed rate of 9 - 10 L / min.
[0038] In Step 3, the specific gravity of the titanium liquid is controlled by the total titanium concentration, and the total titanium concentration is 300 - 320 g / L; the pore size of the filter cake is 10 - 12 nm, and the pore size of the finished product is 1 - 5 nm.
[0039] The present invention has the following key points.
[0040] 1. Phosphorus - sulfur synergistic control process: Use ilmenite raw materials with a phosphorus content < 100 ppm, combined with washing with 3 - 5% ammonia water (or ammonium carbonate / organic amine) to achieve phosphorus < 50 ppm and sulfur < 0.1%.
[0041] 2. Pore size - density regulation method: Through the synergistic effect of vacuum concentration (titanium liquid specific gravity 1.575 - 1.585) and atomization drying (0.2 - 0.4 MPa pressure matching a feed rate of 5 - 10 L / min), obtain a pore size of 1 - 5 nm and a bulk density > 0.8 g / cm³.
[0042] 3. Precursor-carbon source integrated process: Carbon black with a mesh size of 400 - 600 is added when the solid content of the slurry is 20 - 25%, and nano-scale uniform dispersion is achieved through spray drying.
[0043] 4. The secondary slurry is preheated in the pipeline before spraying, and titanium dioxide-carbon black particles are generated after two-stage gradient heating after spraying; the secondary slurry is preheated in the pipeline to 50 - 60 °C before spraying, and first heated to 130 - 150 °C after spraying, and finally heated to 250 - 280 °C to generate titanium dioxide-carbon black particles. After drying, the moisture content of the titanium dioxide-carbon black particles is < 2%.
[0044] It has the following advantages.
[0045] 1. Precise control of impurities: Through the combined process of low-phosphorus ore source (phosphorus content < 100 ppm) and ammonia water washing, the phosphorus content of the finished product is < 50 ppm and the sulfur content is < 0.1%, which is more than 75% lower than that of the traditional process (phosphorus > 200 ppm, sulfur > 0.3%).
[0046] 2. Optimization of pore structure: The synergistic effect of vacuum concentration (specific gravity of 1.575 - 1.585) and atomization drying obtains a pore diameter of 1 - 5 nm and a bulk density of 0.85 g / cm³, and the carbon black mixing index is increased to 97.2% (83.5% in the traditional process).
[0047] 3. Improvement of reaction efficiency: The slurry blending (solid content of 20 - 25%) combined with spray drying enables the titanium carbide yield to reach 99.8% (98.4% in the traditional process), and the particle size distribution D90 < 800 nm.
[0048] 4. Improvement of uniformity and material properties: By preheating, the viscosity of the slurry is reduced, the fluidity is improved, nozzle blockage during spraying is avoided, and the particle size distribution is ensured to be uniform. Through gradient heating, water is slowly evaporated in the first stage (130 - 150 °C) to prevent particles from agglomerating or cracking due to rapid drying; in the second stage (250 - 280 °C), organic substances (such as binders) are carbonized at high temperature to promote the uniform composite of titanium dioxide and carbon black, forming a porous structure and increasing the specific surface area.
[0049] In summary, by controlling the pore diameter of titanium dioxide (1 - 5 nm) and the bulk specific gravity (> 0.8 g / cm³), and cooperating with processes such as atomization drying, preheating, and gradient heating, the carbon black mixing uniformity ≥ 95% is achieved, and the titanium carbide yield is increased to more than 99.5%, greatly improving the quality and yield of the finished titanium carbide.
[0050] Refer to the appendix Figures 1-5, A silicon carbide preparation device, which is used for the above titanium carbide preparation process. It uses a preparation furnace 100. The preparation furnace 100 includes a drying area at the top and a roasting area at the bottom. The secondary slurry is atomized and dried in the drying area to form titanium dioxide-carbon black particles, and the titanium dioxide-carbon black particles flow to the roasting area for roasting to form titanium carbide powder.
[0051] An atomizing drying ring 200 is arranged in the drying area. An annular atomizing drying channel 230 is formed inside the atomizing drying ring 200. An atomizing spray gun 300 is arranged in the atomizing drying channel 230. While the atomizing spray gun 300 atomizes and sprays the secondary slurry, it controls the formation of a spiral drying air flow in the atomizing drying channel 230 to achieve two-stage gradient heating of the titanium dioxide-carbon black particles.
[0052] Here, the atomizing spray gun 300 can blow out heating gas while spraying the secondary slurry in an atomized manner. It is divided into different temperature regions according to the height position of the atomizing drying ring 200. The position temperature of the atomizing spray gun 300 is controlled between 130 - 150 °C, and the position temperature at the top is between 250 - 280 °C. The sprayed secondary slurry can be first heated from the preheated 50 - 60 °C to 130 - 150 °C in a short time. After a certain period of heating and drying, it spirally moves to the top area and is reheated and dried within the temperature range of 250 - 280 °C to finally form the required titanium dioxide-carbon black particles. The moisture content of the finally dried titanium dioxide-carbon black particles is < 2%.
[0053] By preheating, the viscosity of the slurry is reduced, the fluidity is improved, nozzle blockage during spraying is avoided, and the particle size distribution is ensured to be uniform. Through gradient heating, water is slowly evaporated in the first stage (130 - 150 °C) to prevent particles from agglomerating or cracking due to rapid drying; in the second stage (250 - 280 °C), organic substances (such as binders) are carbonized at high temperature to promote the uniform compounding of titanium dioxide and carbon black, form a porous structure, and increase the specific surface area.
[0054] By setting an annular structure, the atomized secondary slurry is controlled to spiral upward, extending the time of gradient temperature rise and avoiding defects in the finished product structure caused by rapid drying of the atomized secondary slurry in a short time.
[0055] Here, the atomizing drying ring 200 includes a first side plate 210 that fits the inner wall of the preparation furnace 100, and also includes an inclined second side plate 220. The atomizing drying channel 230 with an inverted triangular cross-section is jointly formed between the first side plate 210 and the second side plate 220. A blowing structure is also installed in the atomizing drying ring 200, which can form a spiral diversion inside the atomizing drying ring 200. At the same time, cooperating with the negative pressure structure at the bottom of the preparation furnace 100, it can form a spiral upward air flow to drive the rapid drying of the atomized secondary slurry.
[0056] By installing different heating wires at different height positions within the atomization drying ring 200, the temperature gradient change within the atomization drying ring 200 can be controlled; the inner walls of the first side plate 210 and the second side plate 220 here are both sprayed with a non-stick coating structure, and at the same time, tangential air outlets are installed on the inner walls of the first side plate 210 and the second side plate 220, which can avoid the adhesion of the secondary slurry after atomization to the inner wall to the greatest extent and reduce the loss.
[0057] Specifically; the atomization spray gun 300 includes a nozzle 330, a spray gun end 320, and a spray gun base 310. The nozzle 330 is fixedly connected to the spray gun end 320, and the spray gun end 320 is rotatably connected to the spray gun base 310.
[0058] The secondary slurry and the hot air flow are ejected together from the nozzle 330. Here, the atomization spray gun 300 is inclined and installed inside the atomization drying channel 230, and can be tangent to the spiral air flow in the atomization drying channel 230, which can better realize the atomization, dispersion, and drying of the secondary slurry after atomization.
[0059] Here, the spray gun end 320 is rotated unidirectionally by an electric control through a driving component, and an anti-stick coating is also sprayed on the surface of the spray gun end 320. During the rotation process, the position of contact with the air flow is changed, and part of the atomized slurry adhered to the surface can be carried away under the action of the air flow, avoiding continuous accumulation; inside the spray gun end 320 (on the other side where the air flow flows), strip-shaped high-pressure nozzles can also be installed to realize the deep cleaning of the surface of the spray gun end 320 and further avoid residues.
[0060] The spray gun end 320 includes a pump air channel 322 and a slurry channel 321. The slurry channel 321 is annular and sleeved outside the pump air channel 322. The nozzle 330 includes an air jet channel 331 communicating with the pump air channel 322 and a liquid spray channel 332 communicating with the slurry channel 321. The liquid spray channel 332 communicates with the air jet channel 331 and is in a cross state.
[0061] Here, the slurry channel 321 is sleeved outside the pump air channel 322, and the two flow in opposite directions. Under the action of heat diffusion, the hot air flow in the pump air channel 322 can preheat the secondary slurry on the outside to 50 - 60 °C, shortening the subsequent temperature rise range and improving the subsequent atomization drying effect; at the same time, it also avoids excessive temperature rise leading to excessive pressure in the system and ensures the normal operation of the overall system.
[0062] The nozzle 330 further includes a spray sleeve 333 communicating with the air jet channel 331. The spray sleeve 333 is eccentrically arranged outside the rotation axis of the spray gun end 320.
[0063] The hot air flow can pass through the liquid spraying channel 332, then through the air jetting channel 331, and finally be ejected from the spraying sleeve 333. While blowing out a high-speed hot air flow in the air jetting channel 331, the secondary slurry in the liquid spraying channel 332 can be blown out for atomization, realizing the first-stage atomization drying at this position.
[0064] Meanwhile, the spraying sleeve 333 here is eccentrically arranged, which can distribute the atomized slurry at different lateral positions, being suitable for the atomization drying ring 200 with a large internal cross-section, further improving the drying effect of the atomized slurry and shortening the atomization drying time.
[0065] The spray gun base 310 here includes a first conveying channel 311 and a second conveying channel 312, which can be opposite to the slurry channel 321 and the pump air channel 322 respectively. A sealed rotating connector is arranged between them, which can ensure that while the end of the spray gun 320 deflects around the axis, the normal pumping of the hot air flow and the secondary slurry can be guaranteed.
[0066] The present invention will be further described below in combination with specific embodiments and comparative examples. Example 1
[0067] 1. Raw material pretreatment: Take ilmenite with a phosphorus content of 80 ppm, grind it to D50 = 45 μm by ball milling, add 98% sulfuric acid according to an acid-to-ore ratio of 1.6:1, and carry out an acidolysis reaction at 110 °C for 3 hours to generate a mixed solution containing titanyl sulfate.
[0068] 2. Reduction and separation: Add iron powder (the addition amount is 8% of the mass of ilmenite) for reduction, maintain the system temperature at 85 °C and react for 2 hours; then freeze and crystallize at -5 °C for 24 hours to separate and remove ferrous sulfate crystals.
[0069] 3. Hydrolysis control: Add iron powder (the addition amount is 8% of the mass of ilmenite) for reduction, maintain the system temperature at 85 °C and react for 2 hours; then freeze and crystallize at -5 °C for 24 hours to separate and remove ferrous sulfate crystals.
[0070] 4. Washing: Adopt three-stage countercurrent washing: First wash: Wash with a 5% sulfuric acid solution (liquid-solid ratio 3:1); White: Add 0.5% aluminum powder and treat at 80 °C for 1 hour; Second wash: Wash with 4% ammonia water for 55 minutes, and finally control the SO 3 content to 0.07%.
[0071] 5. Atomization drying: Mix the filter cake (pore size 3.2 nm) and 500-mesh carbon black according to Ti:C = 1:2.1 for pulping (solid content 22%), preheat to 55 °C and then atomize and eject at a pressure of 0.3 MPa: Primary drying zone: Stay at 130 - 150 °C for 12 seconds; Secondary carbonization zone: Stay at 270 °C for 8 seconds; Obtain composite particles with a moisture content of 1.8%.
[0072] 6. Carbonization reaction; under a hydrogen atmosphere (H 2 concentration 95%), heat to 1600 °C - 1850 °C at a rate of 15 °C / min and calcine for 2 hours, and complete carbonization by free-falling through the calcination zone.
[0073] Example 2 (High production capacity) The difference from Example 1 is that; Washing optimization; change to washing with 5% ammonium carbonate solution for 50 minutes, and control the SO 3 content to 0.09%. Atomization enhancement; increase the feeding rate to 10 L / min (atomization pressure 0.2 MPa), and use a two-fluid nozzle for atomization: Primary drying zone: high-speed air flow at 140 °C (15 m / s); Secondary carbonization zone: cyclone drying at 260 °C; control the particle moisture content at 2.0%.
[0074] Example 3 (Low impurities) The difference from Example 1 is that; Raw material selection; use super grade ilmenite with a phosphorus content of 50 ppm, and remove iron impurities by magnetic separation (magnetic field intensity 1.2 T).
[0075] Hydrolysis enhancement; add 0.1% sodium polyacrylate dispersant to control the pore size of the metatitanic acid formed by hydrolysis to 2.8 nm.
[0076] Deep washing; use 3% triethylamine organic solution for four-stage washing, and finally: phosphorus content: 18 ppm; sulfur content: 0.04%.
[0077] Precision carbonization; use plasma-assisted heating (power density 50 W / cm²), and reduce the carbonization temperature to 1450 °C.
[0078] Comparative Example 1 (High phosphorus ore source) The difference from Example 1 is that.
[0079] Raw material change; use conventional ilmenite with a phosphorus content of 250 ppm and skip the magnetic separation pretreatment.
[0080] Washing omission; only wash three times with water (no ammonia / ammonium carbonate treatment).
[0081] Comparative Example 2 (No hydrolysis) The difference from Example 1 is that; Hydrolysis out of control; cancel the vacuum concentration step, and the specific gravity of the titanium solution is only 1.52 (total titanium concentration 280 g / L).
[0082] Abnormal atomization; use 0.5 MPa high-pressure atomization, resulting in particle breakage: the pore size expands to 18.6 nm; carbon black agglomerates to form 300 - 500 μm black spots.
[0083] Comparative Example 3 (without preheating) Wrong operation: Cancel the preheating of the slurry pipeline (the original process preheats to 50 - 60°C), and atomize directly at room temperature (25°C).
[0084] Failure manifestations: The slurry viscosity increases (from 12 mPa·s to 38 mPa·s) → the atomized particles are coarse (D90 reaches 2.8 μm); the contact between carbon black and titanium dioxide is insufficient → the mixing index drops to 73.6%; water remains (3.5% after drying) → local oxidation occurs during carbonization → the yield is only 75.8%.
[0085] Comparative Example 4 (without two-stage heating) Wrong operation: Adopt single-stage constant-temperature drying (180°C) and cancel the gradient temperature increase.
[0086] Failure manifestations: The surface of the particles hardens rapidly → internal water is retained (2.8% water after drying); the carbon black distribution shows a gradient difference (the surface carbon concentration is 42% higher than that inside) → the mixing index is 81.2%; the surface area decreases by 28% (compared with Example 1) → the carbon diffusion path is extended → the yield drops to 83.6%.
[0087] Refer to the appendix Figure 7 It can be known that the present invention controls the pore size of titanium dioxide (1 - 5 nm) and the bulk specific gravity (> 0.8 g / cm³), and cooperates with processes such as atomization drying, preheating, and gradient heating to achieve a carbon black mixing uniformity of ≥ 95% and a titanium carbide yield increased to more than 99.5%, greatly improving the quality and yield of the finished titanium carbide.
[0088] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention shall be included within the protection scope of the present invention.
Claims
1. A process for preparing titanium carbide, characterized in that: The steps include: S1. Select ilmenite with phosphorus content less than 100ppm, and generate titanium dioxide filter cake through crushing, reduction, concentration, hydrolysis, washing and filtration; control the pore size of titanium dioxide to 1-5nm, phosphorus content less than 50ppm, and sulfur content less than 0.1%; S2, beating the titanium dioxide filter cake obtained in step S1 to form a primary slurry, adding carbon black according to the content of titanium dioxide and stirring to form a secondary slurry; S3, continuously stirring the secondary slurry, and pumping the secondary slurry into a spray dryer for atomization and drying to generate titanium dioxide-carbon black particles; S4, titanium dioxide-carbon black particles pass through a high temperature calcination zone under the action of airflow and gravity to generate titanium carbide powder; Among them, the secondary slurry is preheated in the pipeline before being sprayed out, and after being sprayed out, it undergoes two stages of gradient heating to generate titanium dioxide-carbon black particles.
2. A titanium carbide preparation process according to claim 1, characterized in that: The secondary slurry is preheated to 50-60°C in the pipeline before being sprayed. After being sprayed, it is first heated to 130-150°C and finally heated to 250-280°C to generate titanium dioxide-carbon black particles. After drying, the moisture content of the titanium dioxide-carbon black particles is less than 2%.
3. A titanium carbide preparation process according to claim 1, characterized in that: A preparation furnace (100) is used, the preparation furnace (100) comprising a drying zone located at the top and a roasting zone located at the bottom, an atomizing drying ring (200) is arranged in the drying zone, an annular atomizing drying channel (230) is formed inside the atomizing drying ring (200), an atomizing spray gun (300) is arranged in the atomizing drying channel (230), and the atomizing spray gun (300) controls the formation of a spiral drying airflow in the atomizing drying channel (230) while spraying the secondary slurry in an atomized manner to achieve two-stage gradient heating of titanium dioxide-carbon black particles.
4. A titanium carbide preparation process according to claim 3, characterized in that: The atomizing spray gun (300) comprises a nozzle (330), a spray gun end (320) and a spray gun base (310); the nozzle (330) is fixedly connected to the spray gun end (320), and the spray gun end (320) is rotatably connected to the spray gun base (310).
5. A titanium carbide preparation process according to claim 4, characterized in that: The spray gun end (320) comprises an air pump channel (322) and a slurry channel (321); the slurry channel (321) is annular and sleeved outside the air pump channel (322); the nozzle (330) comprises an air jet channel (331) connected to the air pump channel (322) and a liquid spray channel (332) connected to the slurry channel (321); the liquid spray channel (332) is connected to the air jet channel (331) and is in a crossed state.
6. A titanium carbide preparation process according to claim 5, characterized in that: The nozzle (330) further comprises a spray sleeve (333) connected to the jet channel (331); the spray sleeve (333) is eccentrically arranged outside the rotation axis of the spray gun end (320).
7. A titanium carbide preparation process according to claim 1, characterized in that: The ilmenite in step S1 is crushed by ball milling, mixed with 98 acid, and initiated by distilled water. The reaction generates a mixture of titanyl sulfate, ferrous sulfate, and ferrous sulfate, which is then leached with water to dissolve the soluble salts. The slurry after leaching is reduced with iron powder; the reduced slurry is separated from the ferrous sulfide by sedimentation, primary filtration, and secondary filtration using a freeze crystallization process.
8. A titanium carbide preparation process according to claim 7, characterized in that: After the titanium liquid is separated from the ferrous sulfide, it is finely filtered and then vacuum concentrated to control the specific gravity of the titanium liquid at 1.575-1.
585. The specific gravity of the titanium liquid is controlled by the total titanium concentration, which is 300-320g / L. A pressurized hydrolysis process is adopted to slowly introduce steam to control the hydrolysis heating rate to not exceed 0.5°C / min. The metatitanic acid after hydrolysis is washed once, bleached and washed twice to control Fe < 30ppm.
9. A titanium carbide preparation process according to claim 8, characterized in that: Second washing: The washed metatitanic acid is pumped into a plate and frame filter press and washed with 3-5% ammonia water for 50-60 minutes. The content of SO3 in the plate and frame titanium dioxide is detected and the SO3 in the plate and frame titanium dioxide is controlled to be less than 0.1%. The pore size of titanium dioxide is detected and the pore size of the titanium dioxide filter cake is 10-12nm and the pore size of the titanium dioxide finished product is 1-5nm. The washed titanium dioxide filter cake is pulped into titanium dioxide slurry and the solid content of the titanium dioxide slurry is controlled to be 20-25%. The calculated carbon black is added and stirred evenly, wherein the carbon black particle size is 400-600 mesh.
10. A titanium carbide preparation process according to claim 1, characterized in that: The secondary slurry atomization drying feed rate is 5-10 L / min, and the atomization pressure is 0.2-0.4 MPa.
Citation Information
Patent Citations
Titanium carbide ceramic microsphere and high-temperature self-propagating preparation method thereof
CN116654936A
Method for preparing titanium pigment by using titanium residues obtained by directly reducing titanium-iron oxide
CN102627321A
Method for preparing titanium carbide or titanium carbonitride
CN103193231A
Method for preparing titanium dioxide through sulfuric acid method
CN103723765A
Titanium dioxide being low in sulfur and super high in specific surface area as well as preparation method and purpose of titanium dioxide
CN107298460A
Cited By
Method for preparing titanium carbide powder from sulfuric acid process titanium dioxide intermediate product
CN121698346A